Digital television, Personal Video Recorders and Media, Automation, Data and Entertainment convergence in the home. (10th December 2008) - Mann, Graham; Bernsteins, Indulis
Out of the confusion of possible delivery technologies for domestic digital video entertainment, the personal video recorder (PVR) with an electronic program guide (EPG) emerges as a key component. Serving as a content manager for video broadcasts, PVRs can automatically record, sort, schedule, store and integrate video material from different sources in a convenient, easy-to-use and timely fashion. Such devices are gradually being adopted in the homes of the developed world, and are the increasing subject of pioneering commercial enterprise, innovative experimentation and open-source community development. Going one step further, the concept of a 'MADE system' is introduced as a system with converged functionality for media, automation, data and entertainment. This article describes and compares three systems with PVR functionality and evaluates their current and future roles as a component for MADE systems. The drivers for and threats to the convergence of functionality towards a MADE system are also considered.